Pendidikan Karakter Religius Sekolah Dasar dalam Perspektif Filsafat Idealisme - Ipung Purwati; Endang Fauziati (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
Religious character education must be applied at all levels of education, especially at the elementary school level. This is because at the elementary school level, they still have a simple mindset so that they have a high chance of being implanted with noble characters. The philosophy of idealism has the same goal as the goal of the Republic of Indonesia, namely to form humans who have noble personalities and have spiritual characters. But in reality, so far the education system in elementary schools has focused more on mastering knowledge, while aspects of religious character seem to have been forgotten. The purpose of this study is to determine the cultivation of religious character education in the perspective of idealism. The results of the study state that religious character and idealistic philosophy are closely related to human morals or noble character.